How Does Left Ventricular Ejection Fraction Affect the Multimodal Assessment of Congestion in Patients with Acute Heart Failure? Results from a Prospective Study - Laura Karla Esterellas-Sánchez; Amelia Campos-Sáenz de Santamaría; Zoila Stany Albines Fiestas; Silvia Crespo-Aznarez; Marta Sánchez-Marteles; Vanesa Garcés-Horna; Alejandro Alcaine-Otín; Ignacio Gimenez-Lopez; Jorge Rubio-Gracia (Applied Sciences)
The assessment of systemic congestion in acute heart failure (AHF) remains clinically challenging, particularly across different left ventricular ejection fraction (LVEF) phenotypes. This study aimed to evaluate whether differences exist in the degree of congestion, assessed through a multimodal approach including physical examination, biomarkers (NT-proBNP, CA125), and point-of-care ultrasound using the Venous Excess Ultrasound (VExUS) protocol, between patients with preserved (HFpEF) and reduced ejection fraction (HFrEF). We conducted a prospective observational study involving 90 hospitalized AHF patients, 80 of whom underwent a complete VExUS assessment. Although patients with HFrEF exhibited higher levels of NT-proBNP and CA125, and more frequent signs of third-space fluid accumulation such as pleural effusion and ascites, no statistically significant differences were found in VExUS grades between the two groups. These findings suggest that the VExUS protocol provides consistent and reproducible information on systemic venous congestion, regardless of LVEF phenotype. Its integration into clinical practice may help refine congestion assessment and optimize diuretic therapy. Further multicenter studies with larger populations are warranted to validate its diagnostic and prognostic utility and to determine its potential role in guiding individualized treatment strategies in AHF.